Pengaruh Model Pembelajaran Inkuiri Terbimbing dengan Metode Eksperimen terhadap Hasil Belajar Fisika Peserta Didik SMA - Nisrina Zuhra; Wahyudi; Ahmad Harjono; Muhammad Zuhdi (Prodi Fisika FKIP Unram, 2021)
This research aimed to determine the effect of guided inquiry learning model with the experimental method on physics learning outcomes of SMA students. This is quasi-experimental research with nonequivalent control group design. The population is all students grade XI MIPA in SMAN 1 Jonggat of academic year 2019/2020 with the sample is students class XI MIPA 4 and class XI MIPA 5 one wich is selected by purposive sampling which is the students class XI MIPA 4 as the experimental group and students class XI MIPA 5 as the control group. The experimental group giving treament with guided-inquiry learning model with the experimental method and control group giving treatment conventional learning. The measured learning otcomes data are the cognitive learning outcomes data. The learning outcomes data are measured in three conditions which is pretest in the form of multiple choice questions, during the learning process with use the LKPD, and posttest in the form of multiple chioice questions as much as 20 items that have been tested for validity. The hypotheses of research were tested using t-test polled variance with 5% significance level. The hypotheses tested result are > that is (4,00 > 2,00) so was rejected and was accepted. The result of hypotheses testing can be concluded there is an influence of guided-inquiry learning model with the experimental method on physics learning outcomes of SMA students. Keywords: Guided-inquiry learning model, experimental methods, learning outcome.